Book Review: Cyanobacteria as Environmental Determinants of Health - Aguilera, Anabella (2018)
Toxic cyanobacterial blooms represent a water quality issue worldwide which incidence and severity are predicted to increase due to climate change and eutrophication (O’Neil et al., 2012). Argentina is not an exception to this trend. Cyanobacterial proliferations have increased in the last two decades as a consequence of water quality changes due to human activities (Otaño et al., 2012; Aguilera et al., 2018). Unfortunately, Argentina lacks specific regulations concerning cyanobacteria and cyanotoxins in freshwater bodies, and information on cyanotoxins occurrence is still scant (Aguilera et al., 2018). This book is the result of the collaborative work between Argentinean researchers and the Ministry of Health who constituted the “Working Group on Health Effects of Cyanobacteria in Water” intended to raise the awareness concerning the increased occurrence of toxigenic cyanobacteria and the threats they pose (Provision 2/2011, Secretariat for Health Relations and Research). The synergy and collaborative interactions within this group have been key steps to promote the establishment of national guidelines for cyanobacterial blooms in drinking and recreational waters